Improving sugarcane productivity on marginal soil in Takalar, Indonesia, through the application of sugarcane factory waste - Safitri, Wina; Ala, Ambo; Gusli, Sikstus; Salim, Iqbal (Journal of Degraded and Mining Lands Management, 2024)
Marginal soil with low nutrient content is a crucial problem in reducing crop productivity, including sugarcane. This study aimed to elucidate the possible improvement of the physical and chemical properties of marginal soil through the application of organic waste from sugar factories, namely kettle ash and press mud. Nine treatment combinations of 0, 10, and 20 t ha-1 of each kettle ash and press mud were arranged in a two-factor randomized factorial design with three replications. Soil organic matter, N, P, and K, soil aggregate stability, and sugarcane productivity were measured after planting sugarcane for five months. The results showed that the application of kettle ash and press mud, especially with a ratio of 20 t ha-1 kettle ash and 10 t ha-1 press mud, was able to reduce the leaching of organic matter and improve sugarcane growth, particularly increasing the number of tillers by 16%, stem height by 14%, and diameter by 16%. The sugarcane productivity obtained was 58.02 t ha-1. Other portions of kettle ash and press mud did not have a favorable effect on sugarcane productivity. This study provided practical insights for increasing agricultural productivity, especially in sugarcane plantations.